Neurotoxic effects of levobupivacaine and fentanyl on rat spinal cord - Abut,Yesim Cokay (2015)
BACKGROUND: The purpose of the study was to compare the neurotoxic effects of intrathecally administered levobupivacaine, fentanyl and their mixture on rat spinal cord. METHODS: In experiment, there were four groups with medication and a control group. Rats were injected 15 µL saline or fentanyl 0.0005 µg/15 µL, levobupivacaine 0.25%/15 µL and fentanyl 0.0005 µg + levobupivacaine 0.25%/15 µL intrathecally for four days. Hot plate test was performed to assess neurologic function after each injection at 5th, 30th and 60th min. Five days after last lumbal injection, spinal cord sections between the T5 and T6 vertebral levels were obtained for histologic analysis. A score based on subjective assessment of number of eosinophilic neurons - Red neuron - which means irreversible neuronal degeneration. They reflect the approximate number of degenerating neurons present in the affected neuroanatomic areas as follows: 1, none; 2, 1-20%; 3, 21-40%; 4, 41-60%; and 5, 61-100% dead neurons. An overall neuropathologic score was calculated for each rat by summating the pathologic scores for all spinal cord areas examined. RESULTS: In the results of HPT, comparing the control group, analgesic latency statistically prolonged for all four groups.In neuropathologic investment, the fentanyl and fentanyl + levobupivacaine groups have statistically significant high degenerative neuron counts than control and saline groups. CONCLUSIONS: These results suggest that, when administered intrathecally in rats, fentanyl and levobupivacaine behave similar for analgesic action, but fentanyl may be neurotoxic for spinal cord. There was no significant degeneration with levobupivacaine, but fentanyl group has had significant degeneration.